Acupuncture for the Treatment of Neuropsychiatric Symptoms in Parkinson's Disease: A Systematic Review and Meta-Analysis - Anxin Zhang; Zefeng Song; Anqi Di; Zelin Zhou; Liang Zheng; Lixing Zhuang (Elsevier, 2024)
Background: Neuropsychiatric symptoms (NPSs) of Parkinson's disease (PD) have received increasing attention, but effective treatment options remain limited. Acupuncture may have clinical benefits for NPSs in PD patients, but high-quality evidence supporting this possibility still needs to be discovered. Therefore, we conducted a meta-analysis to evaluate the effect of acupuncture treatment on NPSs in PD patients. Methods: Randomized controlled trials (RCTs) of acupuncture treatment for PD retrieved from the following electronic databases: PubMed, Embase, Cochrane Library, Web of Science, and Scopus, were used to evaluate NPSs of PD patients. The Cochrane Intervention System Evaluation Manual assessed the methodological quality. Results: A total of 13 RCTs involving 719 patients were included. The results showed that compared with medication alone or sham acupuncture, acupuncture improved sleep quality in PD patients, with Parkinson's Disease Sleep Scale (PDSS) [standardized mean difference (SMD)= 0.48, 95% confidence interval (CI)= 0.242 to 0.793, P = 0.001]. The I scores and total scores on Unified Parkinson's Disease Rating Scale (UPDRS) indicated acupuncture treatment was effective (SMD=−0.66, 95%CI=−0.66 to −0.18, P = 0.042; SMD=−0.77, 95%CI=−1.31 to −0.23, P = 0.005). Results of the Epworth Sleepiness Scale (ESS) and Parkinson's Disease Questionnaire-39 (PDQ-39) showed no statistically significant differences (SMD=−0.27, 95%CI=−0.08 to 0.62, P = 0.128; SMD=−0.20, 95%CI=−0.42 to 0.01, P = 0.554). Anxiety and depression research had no significant differences due to the excessive inter-study bias. Conclusion: Acupuncture treatment can improve sleep quality, psychological and behavioral alterations, and the overall condition of PD patients. However, the study revealed no significant positive intervention effects on anxiety, depression, and quality of life, underscoring the necessity for continued research to elucidate these domains' intricacies and develop productive therapeutic approaches.